Analisis Faktor-Faktor Tunggakan Rekening Air Pada Perusahaan Daerah Air Minum (PDAM) Tirtanadi Provinsi Sumatera Utara: Studi Kasus pada PDAM Tirtanadi Cabang HM Yamin - Aulia Ramadani Pane; Nur Fadhillah Ahmad Hasibuan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
PDAM Tirtanadi is a company that provides clean water services to the general public, especially residents of HM Yamin and the surrounding area. PDAM Tirtanadi runs its operations with profits from customers who use its services. However, due to the large number of customer arrears, especially at the HM Yamin branch, the income received by PDAM Tirtanadi is less. The aim of this research is to identify variables that have the potential to cause customer water account arrears at the Tirtanadi Regional Drinking Water Company (PDAM) HM Yamin Branch. This study uses qualitative descriptions. In addition, during the research process, this research was carried out through observations, interviews and interviews, and document analysis. The research results show that the factors that cause water bill arrears include; 1) Customer economics; 2) Water is not running; 3) Water quality; 4) Buried meters; 5) Customer behavior to delay payment; and 6) Usage soars.